Psychologie spotřebitele - Navrátilová, Irena (Univerzita Pardubice, 2006)
Hlavním cílem práce je ukázat několik hlavních aspektů, které nás jako spotřebitele nejvíce ovlivňují. Jakou roli v nákupním procesu hrají duševní vlastnosti, životní zkušenosti i to jak na spotřebitele působí okolní svět.

The principal objektive of this work was to present some of general aspects the consumer is mostly influenced by. Which part in the purchasing process do the psychical characters and life experiences have, and also how the consumer is affected by his surroundings.
Psychology of consumer
Keywords: consumers; products; brands; prices; Advertisings; questionnaire investigations; spotřebitelé; produkty; značky; Ceny; reklamy; dotazníková šetření